2021
DOI: 10.1002/ajcp.12492
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Adolescent Masculinities and Associations with Internalizing Behavior Problems and Social Support

Abstract: Interest in the connection between masculinities and mental health continues to grow. However, no previous systematic review has explored this association for adolescents. We present the systematic review of 29 articles that explore the connection between adherence to stereotypical male gender role norms (e.g., emotional restriction), attributes (e.g., “ambitious”), and identity (most commonly, gender “typicality”) and internalizing behavior problems and social support. A total of 24,795 adolescent boys (6th‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…When emotion was displayed, boys who endorsed highly hegemonic masculine ideas tend to feel that anger was the only acceptable emotion, leading such boys to be less likely to back down from a physical fight when challenged. Research on hegemonic masculinity in young children is limited, but does find the beginnings of similar attitudes and patterns displayed by adults, such as increased internalizing problems (Exner-Cortens, Wright, Claussen, & Truscott, 2021). For example, one study of middleschool-aged children (seventh and eighth grade) found that children who prescribed more masculine norms (especially emotional stoicism) decreased both school liking and engagement (Rogers, Updegraff, Santos, & Martin, 2017).…”
Section: Themes Of Hegemonic Masculinity In Princess Mediamentioning
confidence: 99%
“…When emotion was displayed, boys who endorsed highly hegemonic masculine ideas tend to feel that anger was the only acceptable emotion, leading such boys to be less likely to back down from a physical fight when challenged. Research on hegemonic masculinity in young children is limited, but does find the beginnings of similar attitudes and patterns displayed by adults, such as increased internalizing problems (Exner-Cortens, Wright, Claussen, & Truscott, 2021). For example, one study of middleschool-aged children (seventh and eighth grade) found that children who prescribed more masculine norms (especially emotional stoicism) decreased both school liking and engagement (Rogers, Updegraff, Santos, & Martin, 2017).…”
Section: Themes Of Hegemonic Masculinity In Princess Mediamentioning
confidence: 99%
“…The role of toxic masculinity regarding mental health has been previously investigated. Toxic masculinity is associated with reduced mental well-being and less help-seeking behaviors [ 28 ], and are harmful to men and those around them [ 29 ]. However, research has shown that men’s health improves when they participate in egalitarian groups that foster alternative masculinities and friendship relationships [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Themes of freedom to be oneself and express emotions also align with past qualitative WiseGuyz work, but we found that the photo-based method allowed participants to more clearly articulate their perceived growth in these areas. As emotional restriction and lack of social support are likely key causes of adverse outcomes related to strong adherence to stereotypical male gender role norms ( Evans et al, 2010 ; Exner-Cortens, Wright, et al, in press ; Wong et al, 2017 ), participants’ emphasis on the emotional freedom they felt after participating in WiseGuyz is an especially promising finding.…”
Section: Discussionmentioning
confidence: 99%